Feed evaluation science - Moughan, Paul J.; Hendriks, Wouter H. (Brill | Wageningen Academic, 2018)
Written by a team of international authorities, Feed Evaluation Science, is a must-have for students, researchers, postdoctoral fellows and teachers of animal nutrition, as well as practitioners in the feed industry. The text offers a classical treatment of the basic principles and new developments in feed evaluation for simple-stomached animals with emphasis on pigs and poultry. The chapters follow a logical progression, to provide a coherent in-depth coverage of the key science and technology inherent in the nutrition and feeding of animals. The topics covered are nutrient analysis and characterisation, nutrient-bioavailability, post-absorptive nutrient utilisation, the principles of animal growth and the mathematical modelling of growth. Practical aspects of feed processing, anti-nutritional factors, the use of markers in nutrition studies, predicting bioavailable nutrients and the principles of feed formulation are highlighted in the context of pig, poultry and companion animal nutrition. This is a classic text on the nutrition of simple-stomached animals, and is intended for those working at the forefront of developments in feed evaluation science."